Characterisation and in vitro cytotoxicity of toxic and degradation compounds in bamboo shoots (Dendrocalamus Sinicus) during traditional fermentation. (30th August 2020) - Yi, Junjie; Li, Meiqi; Yang, Meilian; Cai, Shengbao; Zhao, Tianrui; Cao, Jianxin; Cheng, Guiguang
Summary: Fermentation has been historically applied to reduce bamboo shoot (BS) toxicity. However, the underlying degradation pathway of the toxic compounds remains unknown. In this work, the cytotoxicity of BS against the BRL‐3A cells was evaluated, and the changes in chemical constituents were determined to reveal the influence of fermentation on BS. The in vitro toxic evaluation revealed fermentation time was crucial in decreasing the toxicity. The main compounds in fresh and fermented were qualitatively and quantitatively determined and were further targeted isolated and identified. A mathematical model to describe the change rate as a function of fermentation time was formulated. Dynamic profiling revealed that taxiphyllin 1, p ‐hydroxybenzaldehyde 2 and methyl‐ p ‐hydroxybenzoate 3 decreased and transformed into intermediate compounds ( p ‐hydroxybenzoic acid 4 and p ‐hydroxybenzyl alcohol 5 ), finally converting into p ‐hydroxytoluene 6 during fermentation. The results provided basis on the chemical components for practical fermentation and the quality control of BS products. Abstract : Bamboo shoots are degraded by traditional fermentation methods, and the transformation of main compounds in the fermentation process is studied.